Disaster in Javanese Mythological Narratives: Learning from Semeru Eruptions - Zulianto, Mukhamad; Suharso, Pudjo; Thoharudin, Munawar; Yushardi, Yushardi (Yayasan Keluarga Guru Mandiri, 2026)
This study explores the integration of environmental ethics, cultural traditions, and technological innovation in disaster mitigation education to enhance the resilience of communities vulnerable to natural disasters, particularly those near Mount Semeru. Employing a qualitative methodology with a phenomenological approach, this research examines Javanese cultural perspectives on human-nature relationships and their implications for disaster preparedness. Data collection involved interview with village elders, community leaders and village youth, document analysis of Javanese philosophical texts, mythology, and oral traditions, as well as expert consultations with scholars in Javanese cosmology and disaster education. Thematic and comparative analyses were conducted to identify key patterns in disaster perception and response. The findings reveal that the Semeru community’s mitigation strategies are deeply rooted in traditional wisdom, classified into narrative, mystical, and functionalistic guidance, forming the basis of the ‘Triple N’ model: Nuturi, Niteni, and Nindaki. This framework emphasizes socialization, internalization, and enculturation to strengthen disaster awareness and community leadership. The study contributes to disaster education by bridging traditional knowledge with modern mitigation strategies, offering a culturally grounded approach that enhances community preparedness and response effectiveness. The Triple N model offers a culturally grounded framework that enhances disaster education, strengthens community resilience, and supports the development of a disaster mitigation curriculum.